2020
DOI: 10.1126/sciadv.aaz4948
|View full text |Cite
|
Sign up to set email alerts
|

A general approach for hysteresis-free, operationally stable metal halide perovskite field-effect transistors

Abstract: Despite sustained research, application of lead halide perovskites in field-effect transistors (FETs) has substantial concerns in terms of operational instabilities and hysteresis effects which are linked to its ionic nature. Here, we investigate the mechanism behind these instabilities and demonstrate an effective route to suppress them to realize high-performance perovskite FETs with low hysteresis, high threshold voltage stability (ΔVt < 2 V over 10 hours of continuous operation), and high mobility value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
171
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(180 citation statements)
references
References 61 publications
1
171
0
Order By: Relevance
“…[1][2][3][4][5] However, perovskitebased thin-film transistors (TFTs) have drawn less research attention, despite the high intrinsic charge carrier mobility. [6][7][8] This is mainly due to the difficulty in obtaining a reliable transistor operation with spin-coated perovskite films as a result of ion migration under bias, poor ambient stability of the material, and bulk and interfacial defects. The ion migration and accumulation at the perovskite and dielectric interface tend to screen the applied gate field, resulting in poor and unreliable channel current modulation at room temperature and significant dual-sweep current-voltage hysteresis.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] However, perovskitebased thin-film transistors (TFTs) have drawn less research attention, despite the high intrinsic charge carrier mobility. [6][7][8] This is mainly due to the difficulty in obtaining a reliable transistor operation with spin-coated perovskite films as a result of ion migration under bias, poor ambient stability of the material, and bulk and interfacial defects. The ion migration and accumulation at the perovskite and dielectric interface tend to screen the applied gate field, resulting in poor and unreliable channel current modulation at room temperature and significant dual-sweep current-voltage hysteresis.…”
mentioning
confidence: 99%
“…introduced Rb doping to fabricate Rb 0.05 Cs 0.05 FA 0.15 MA 0.75 PbI 3 transistor, where the hysteresis is nearly removed with a room temperature mobility of ≈1.2 cm 2 V −1 s −1 . [ 206 ] Recently, authors’ group have reported a very high mobility of 32.25 cm 2 V −1 s −1 with an on/off ratio greater than 10 7 by incorporating carbon nanotubes (CNT) into (MA 1− x FA x )Pb(I 1− x Br x ) 3 perovskite. [ 207 ] All‐inorganic perovskite materials also exhibited environmental stability and electronic properties compared to organohalide perovskites.…”
Section: Perovskite‐based Transistorsmentioning
confidence: 99%
“…[53] It was also found that following an initial decay, the channel current can also increase due to healing of vacancies upon ion migration and/or reduction in contact resistance. [52] Ion migration is closely interlinked with the defect chemistry of the perovskite layer. In metal halide perovskites iodide interstitials (I I -) and vacancies (V I -) possess very low formation energies, therefore these species dominate the defect physics.…”
Section: Ionic Defects and Ion Migration: Impact On Perovskite Fet Operationmentioning
confidence: 99%
“…Early studies quickly realized that screening of the electronic transport by ionic migration, along with the structural fluctuations and dynamical disorder (rotations of the MA unit around its axis and PbX 6 octahedral distortions) make electrostatic gating of lead-based 3D perovskites non trivial. [27,29,30,53,92,93] These phenomena are thermally activated, and thus can be reduced and often even suppressed upon decreasing the temperature, resulting in several early studies reporting on the performance at 70-80 K. [27,53] Recent advances in material and device engineering have led to more reliable transistor behavior, with low hysteresis and charge carrier mobilities >1 cm 2 V -1 s -1 at room temperature, [33,52,74,94] which allowed investigations of temperature-related effects. Temperature dependent studies provide important details about the charge transport mechanism in perovskite materials, which remains elusive.…”
Section: Effect Of Temperaturementioning
confidence: 99%